Capnocytophaga canimorsus meningitis diagnosed using next- generation sequencing of microbial cell-free DNA. (2021) - Asif, Abuzar A.; Roy, Moni; Tellier, Benjamin R.; Ahmad, Sharjeel
Abstract: Capnocytophaga canimorsus meningitis is frequently caused by exposure to dog or cat bites and occurs more commonly in immunocompromised individuals. CSF analysis is the first step in diagnosis; however, in situations where CSF cultures turn negative, molecular techniques such as 16S rRNA gene amplification followed by polymerase chain reaction (PCR) product sequencing have shown promise. Next generation sequencing of cell free DNA (NGS cfDNA) can assist in identifying the causative agent in a quick and accurate manner. We present a rare case of C. canimorsus meningitis in an immunocompetent host that highlights the utility of NGS cfDNA in timely diagnosis after exhausting all other available diagnostic techniques.